2004
DOI: 10.1158/0008-5472.can-03-3259
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1/B7H-1 Inhibits the Effector Phase of Tumor Rejection by T Cell Receptor (TCR) Transgenic CD8+ T Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
504
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 697 publications
(542 citation statements)
references
References 40 publications
17
504
0
1
Order By: Relevance
“…One possibility that could explain why LIGHT treatment does not work on large tumors is due to the fact that LIGHT increases the level of IFN-γ ( Figure 5G), which can also promote PD-L1 upregulation as part of the adaptive resistance mechanism (Blank et al, 2004). We hypothesized that LIGHT might trigger inhibitory signals as a negative feedback mechanism, which in turn can dampen the initial antitumor effects on large tumors.…”
Section: Light Overcomes Tumor Resistance To Anti-pd-l1 By Increasingmentioning
confidence: 99%
“…One possibility that could explain why LIGHT treatment does not work on large tumors is due to the fact that LIGHT increases the level of IFN-γ ( Figure 5G), which can also promote PD-L1 upregulation as part of the adaptive resistance mechanism (Blank et al, 2004). We hypothesized that LIGHT might trigger inhibitory signals as a negative feedback mechanism, which in turn can dampen the initial antitumor effects on large tumors.…”
Section: Light Overcomes Tumor Resistance To Anti-pd-l1 By Increasingmentioning
confidence: 99%
“…Depending on the model system, PD-L1 and PD-L2 were initially reported to have inhibitory or stimulatory effects on T cell responses (13,14). Recent reports on PD-L1 using knockout mice or in vivo studies with blocking anti-PD-L1 mAbs have been consistent with an inhibitory role for PD-L1 (13,16,(21)(22)(23)(24)(25)(26). Recent reports on PD-L2 using knockout mice or blocking mAbs still find opposing functions (27,28).…”
Section: Pd-1:pd-l1 Interactionsmentioning
confidence: 99%
“…Anti-CTLA-4 treatment has been trialled in melanoma and other cancers with some evidence of clinical efficacy (Wolchok and Saenger, 2008;Yuan et al, 2008). The expression of PD-L1 (B7-H1), a ligand for PD-1, is upregulated by IFN-g (Blank et al, 2004) and has been observed in many tumour types, often being associated with a poor prognosis (Zou and Chen, 2008). PD-1/PD-L1 interactions impair anti-tumour T-cell responses in mice, which is reversed in PD-1-deficient mice or by blocking PD1 (Blank et al, 2004).…”
Section: Activated T Cells May Be Switched Off By Some Tumoursmentioning
confidence: 99%
“…The expression of PD-L1 (B7-H1), a ligand for PD-1, is upregulated by IFN-g (Blank et al, 2004) and has been observed in many tumour types, often being associated with a poor prognosis (Zou and Chen, 2008). PD-1/PD-L1 interactions impair anti-tumour T-cell responses in mice, which is reversed in PD-1-deficient mice or by blocking PD1 (Blank et al, 2004). Mechanistically, expression of PD-L1 by tumours induces T-cell apoptosis (Dong et al, 2002), induces production of IL-10 and may mediate regulatory T cell (Treg)-suppressive activity (Zou and Chen, 2008).…”
Section: Activated T Cells May Be Switched Off By Some Tumoursmentioning
confidence: 99%